2021
DOI: 10.21037/cdt-20-728
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency of quantification of myocardial blood flow and coronary flow reserve with CZT dynamic SPECT imaging for patients with suspected coronary artery disease: a comparative study with traditional semi-quantitative evaluation

Abstract: Background: Myocardial blood flow (MBF) quantitation with cadmium-zinc-telluride (CZT) dynamic single-photon emission computed tomography (SPECT) is being increasingly investigated toward clinical utilization.Methods: In this prospective study, forty-nine patients with suspected or known coronary artery disease (CAD) underwent a rest/adenosine triphosphate (ATP) stress dynamic and routine gated myocardial perfusion imaging (MPI) by CZT SPECT and then received coronary angiography (CAG). Quantitative diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
4
9
0
1
Order By: Relevance
“…In line with the previous study by Stewart et al where the comparison in rest and stress MBF (by PET with 13 N-ammonia) were performed on the day 9 after PCI in infarct-related and reference artery (5), we found out significantly reduced MBF, MFR and FD (both AC and NAC) (8,9,11,20), invasive angiography (19,(35)(36)(37) and invasive FFR (8,(38)(39)(40).…”
Section: Myocardial Blood Flow In Acute Coronary Syndromesupporting
confidence: 92%
“…In line with the previous study by Stewart et al where the comparison in rest and stress MBF (by PET with 13 N-ammonia) were performed on the day 9 after PCI in infarct-related and reference artery (5), we found out significantly reduced MBF, MFR and FD (both AC and NAC) (8,9,11,20), invasive angiography (19,(35)(36)(37) and invasive FFR (8,(38)(39)(40).…”
Section: Myocardial Blood Flow In Acute Coronary Syndromesupporting
confidence: 92%
“…19 Another point to emphasize is that, although the optimal cut-off values for MBF and MFR were validated using regadenoson as stress agent, 15 several studies observed that dipyridamole, regadenoson, and adenosine can induce an equivalent level of hyperemia and similar performance in the detection of CAD. 14,18,20 In the current study, Liu et al 17 confirmed the feasibility of dipyridamole as stress agent finding a positive correlation between the change of heart rates from rest to stress state and the global MFR as well as DMBF.…”
supporting
confidence: 70%
“…The value of nuclear medicine MPI in the noninvasive function evaluation of CAD has been recognized internationally (15). With the continuous innovation of nuclear medicine imaging equipment as a novel technology, CZT-SPECT quantitative myocardial flow technique shows a great application prospect in clinical MFR evaluation (10,15). Thus far, data from extensive sample epidemiological studies on CMD remain lacked (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, in routine outpatient follow-up, considerable post-PCI patients with recurrent chest pain had normal CAG, as recognized by doctors as "non-cardiogenic chest pain" and ignored, thereby causing repeated visits without adequate treatment (18). CZT-SPECT-based MFR could help doctors differentiate and identify high-risk patients, thereby being worthy of widespread clinical application (10,19). Figure 3 illustrates a typical case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation